2021
DOI: 10.1038/s42003-020-01534-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modulates stress response in mainstream anammox reactors

Abstract: Autotrophic nitrogen removal by anaerobic ammonium oxidizing (anammox) bacteria is an energy-efficient nitrogen removal process in wastewater treatment. However, full-scale deployment under mainstream conditions remains challenging for practitioners due to the high stress susceptibility of anammox bacteria towards fluctuations in dissolved oxygen (DO) and temperature. Here, we investigated the response of microbial biofilms with verified anammox activity to DO shocks under 20 °C and 14 °C. While pulse disturba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 77 publications
1
6
1
Order By: Relevance
“…In particular, divergent responses of the hzs complex and hdh gene to other shocks or disturbances have been discovered. In contrast to our observations in this study, decreased transcriptional activities of the hzs complex and upregulation or downregulation of hdh gene expression were observed when the anammox bacteria were subjected to a lower temperature regime (20 °C to 14 °C) or DO exposure [ 24 , 25 ]. These effective regulation strategies are able to alleviate the negative impacts of stress conditions on the anammox bacteria.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, divergent responses of the hzs complex and hdh gene to other shocks or disturbances have been discovered. In contrast to our observations in this study, decreased transcriptional activities of the hzs complex and upregulation or downregulation of hdh gene expression were observed when the anammox bacteria were subjected to a lower temperature regime (20 °C to 14 °C) or DO exposure [ 24 , 25 ]. These effective regulation strategies are able to alleviate the negative impacts of stress conditions on the anammox bacteria.…”
Section: Discussioncontrasting
confidence: 99%
“…Understanding the transcriptional responses of anammox consortia during disturbances as well as the synergetic interactions between microorganisms is crucial for understanding the capacity of anammox consortia in response to stress and system stability. The integrated strategy has been used to investigate the stress (e.g., DO, temperature, or nutrient limitation) responses of anammox bacteria at various biological levels and the subsequent recovery process [ 24 27 ]. However, few studies have revealed the effect of starvation caused by short-term nutrient deprivation (e.g., caused by system failures) on the anammox system, especially using multi-omics strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome and virome analyses showed that the chemical pretreatments and AD substantially influenced the assemblages of bacterial and viral communities in FS. Similarly, previous studies also indicated that the changes in microbial co-occurrence networks and community assemblages enhanced microbiome resilience of sewage sludge to oxygen and temperature fluctuations. Spore-forming Romboutsia and Clostridium could tolerate the ALK and NaClO pretreatments (Figure e), but both genera were suppressed after AD. In contrast to the findings for non-spore-forming bacteria, Escherichia and Shigella abundance was decreased by ALK-P and NaClO-P pretreatments but not by AD (Figures e and S10).…”
Section: Discussionsupporting
confidence: 63%
“…Meanwhile, ΔNO 2 − ‐N/ΔNH 4 + ‐N was 1.66 ± 0.42, 1.29 ± 0.12, 1.46 ± 0.28 and 1.45 ± 1.45, and ΔNO 3 − ‐N/ΔNH 4 + ‐N was 0.03 ± 0.33, 0.08 ± 0.13, 0.24 ± 0.19 and 0.50 ± 0.22, respectively. These findings could be attributed to the challenge of NOB reproduction 22,23 . In fact, at lower substrate concentrations, the higher proportions of NO 2 − ‐N will be consumed by NOB using the equivalent amount of DO in influent, thus reducing the available NO 2 − ‐N for AnAOB and ultimately leading to lower TNRE under the lower substrate conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These findings could be attributed to the challenge of NOB reproduction. 22,23 In fact, at lower substrate concentrations, the higher proportions of NO 2 − -N will be consumed by NOB using the equivalent amount of DO in influent, thus reducing the available NO 2 − -N for AnAOB and ultimately leading to lower TNRE under the lower substrate conditions. -N consumed by NOB was prior to AnAOB, which was influenced by the EBCT decrease resulting in substrate competition between AnAOB and NOB escalating.…”
Section: A-bf Performance With Substrate Concentration Decreasementioning
confidence: 99%